Single Crystal Perovskite Microplate for High‐Order Multiphoton Excitation. Issue 12 (23rd July 2019) - He, Huajun; Ma, En; Chen, Xueyuan; Yang, Deren; Chen, Banglin; Qian, Guodong
Abstract: Single crystal perovskite microplates are fundamentally and technologically very important to developing high‐order ( n ≥ 3) multiphoton excitation. This study reports the preparation of high‐quality single crystal perovskite microplates through the controlled release of lead ions from the confined species within a metal–organic framework. The resulting free‐standing MAPbBr3 (MA = CH3 NH3 + ) and CsPbBr3 single crystals of rectangular microplates exhibit excellent multiphoton excitation behaviors, as demonstrated in their five‐photon‐excited photoluminescence and three‐photon‐pumped stimulated emission with the threshold of 159 mJ cm −2, providing the promise of exploring high‐quality single crystal perovskite microplates for functional optoelectronic and photonics applications. Abstract : High‐quality perovskite single crystal microplates with high‐order multiphoton excitation response are prepared via the metal–organic framework confinement strategy. The resulting free‐standing MAPbBr3 and CsPbBr3 microplates not only possess identical rectangular platelet morphology, but also exhibit excellent high‐order multiphoton excitation performance, as demonstrated in five‐photon‐excited photoluminescence and three‐photon‐pumped stimulated emission.